2016
DOI: 10.21511/bbs.11(2).2016.03
|View full text |Cite
|
Sign up to set email alerts
|

Financing and financial sustainability of microfinance institutions (MFIs): a conceptual view

Abstract: Recent evidence shows that MFI financing continues to evolve with an increased inclination towards commercial financing. Taking stock on MFI financing and refocusing on the relationship between financing options and financial sustainability (FS) is unavoidable. The authors consummated a literature review based on complementing the little evidence on the subject with both theoretical and implied evidence from related studies in unpacking the relationship. Though donations are losing grip as a popular MFI financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This result concurs with the findings of Dawar (2014). Interestingly, Bassem (2012), Adhikary et al (2014) and Bayai et al (2016a) found dissimilar results noting that the financial performance of new microfinance institutions is poor because of low technology, lack of sufficient capital, small client base and operational challenges.…”
Section: Transformation Of Microfinance Ngos and Return On Assetssupporting
confidence: 79%
See 1 more Smart Citation
“…This result concurs with the findings of Dawar (2014). Interestingly, Bassem (2012), Adhikary et al (2014) and Bayai et al (2016a) found dissimilar results noting that the financial performance of new microfinance institutions is poor because of low technology, lack of sufficient capital, small client base and operational challenges.…”
Section: Transformation Of Microfinance Ngos and Return On Assetssupporting
confidence: 79%
“…Deposits to total assets ratio indicates the segment of the capital structure of the microfinance institution that is financed by public savings (Bogan, 2012;Awaworyi et al, 2014). Deposits provide cheaper sources of funding and as such lowers the cost of operations for microfinance institutions and in return increase the financial sustainability of the microfinance institutions through increased profitability (Helms, 2006;Bayai et al, 2016a). Therefore, the study expected a positive effect of deposits to total assets ratio on the indicators of financial performance (Awaworyi et al, 2014).…”
Section: Explanation and Operationalization Of The Study Variablesmentioning
confidence: 99%
“…The provision of financial services to the poor is based on the assumption that MFIs exist on a going concern principle to solve social problems such as poverty, unemployment, and low living standards. Being financially sustainable does not limit outreach to the poor; rather, it advances outreach [14], since the poor need to have access to financial service on a long-term basis rather than just short-term financial support [15]. Financial sustainability is necessary to reach significant numbers of poor people on a permanent basis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of members and financing funds has a positive effect on BMT profitability (Bayai & Ikhide, 2016). However, on the other hand, a growth in financing also has the potential to raise the financing risk (non-performing financing) if it is not managed properly.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research, there are various aspects involved in achieving IMFI sustainability. These include financial, social and spiritual intermediation (Wediawati, Effendi, Herwany, & Masyita, 2018), the implementation of good governance to maintain the financial sustainability of IMFIs and minimise the various risks that exist (Kassim, Hassan, & Kassim, 2018), organisational and social performance (Bouljelbene & Fersi, 2016), a solid overall performance in order to sustain the institution financially and operationally as well as ensure progress and growth (Ascarya, 2014), the financing structure in place (Bayai & Ikhide, 2016), outreach to the poor (Kipesha & Zhang, 2013), greater capital intensity and a higher number of employees (Mia, Nasrin, & Cheng, 2016), monitoring cost, regulation and supervision (Nabi & Zouari, 2013), social capital and spiritual wellbeing (Rahman, Al Smady, & Kazemian, 2015), and service quality (Nurfadilah, Samidi, & Subagja, 2018).…”
Section: Previous Studymentioning
confidence: 99%